Prevention of Canine Coronary Artery Thrombosis with Echistatin, a Potent Inhibitor of Platelet Aggregation from the Venom of the Viper, Echis carmatus - Shebuski, Ronald J; Ramjit, Denise R; Sitko, Gary R; Lumma, Patricia K; Garsky, Victor M (Thrombosis and Haemostasis, 1990)
A model of acute, platelet-dependent canine coronary artery thrombosis was utilized to assess the antithrombotic effect of a synthetic, RGD-containing 49-residue protein termed echistatin. This protein is derived from the venom of the viper, Echis carinatus. In vitro, echistatin inhibited ADP (10 ΜM)-induced platelet aggregation with IC50 values in human and canine platelet-rich plasma of 101 ± 4 and 127 ± 32 nM, respectively. In vivo, in the dog, infusion of echistatin for 30 min at 20 pg kg−1 min−1 or 2.6 nM kg−1 min−1 resulted in total abolition of acute platelet-dependent coronary thrombus formation in all dogs tested (n = 5). Infusion of a lower dose (10 pg kg−1 min−1) was not effective in prevention of thrombus formation. Blood samples were taken before and after infusion of echistatin in order to determine ex vivo platelet aggregatory responses. Echistatin (20 pg kg−1 min−1, i.v.) attenuated ex vivo platelet aggregation elicited by ADP, U-46619 and collagen and increased bleeding time by 2.9 ± 0.5-fold over control. Thus, in the dog, echistatin is an effective antithrombotic agent inhibiting both platelet aggregation in vivo in the coronary artery as well as ex vivo with a concomitant increase in bleeding time. Furthermore, the effects of echistatin on platelet aggregation and bleeding time are reversible with restoration to control levels occurring 30-60 min after termination of the infusion.